Bridging the Gap between Local Public Health and the Healthcare Community: The Public Health Talk - Puja Bharucha; Rachel Franklin (Georgia Southern University, 2016)
Background: District epidemiologists often rely on healthcare providers for medical information regarding reportable diseases in order to properly investigate cases. It becomes difficult when providers do not share patient information due to apprehension and/or lack of knowledge of HIPAA exemption laws. It is also challenging when the provider staff is not knowledgeable regarding disease specific information. When information is withheld, there is a delay in completing investigations, and high priority cases and outbreaks such as emerging infectious diseases can be missed or lost to follow up. Methods: The Public Health Talk (The Talk) initiative was established at Cobb and Douglas Public Health in 2014 by the Epidemiology Department. The Talk includes a comprehensive binder that consists of information about the reportable diseases, emerging infectious diseases, sexually transmitted infections and provides guidelines and protocols as recommended by the Georgia Department of Public Health. It provides a forum for local epidemiologists to informally meet and educate staff of healthcare facilities (physicians, nurses, office managers, administrative assistants, etc). Pre-talk and post-talk surveys were developed to assess knowledge gained of the staff to which The Talk was presented. Results: The initiative is ongoing, however, 31 Talks were completed by March 2016, but only 8 facilities were evaluated due to the delayed development of the surveys. It was found that 38% of staff members were not aware of the reportable diseases prior to the Talk. There was a noted increase in knowledge of local public health and the resources that are offered to healthcare facilities. Conclusions: Healthcare providers have begun to utilize public health to aid in assessing and diagnosing diseases. The initiative is evolving and continuously improving, including the development of newsletters to improve communication and the resource binder will be reorganized to have specific information that is needed by the specialty of the provider.